The Impact of Climate Change on The Mental and Physical Health in Human Being: A review - Muhsin, Eman A. (Al-Salam Journal for Medical Science, 2024)
A major worldwide concern of our day is climate change. It is regarded as a problem for both human health and the environment. Assessing the effects of climate change on humans and other living things becomes imperative. Nowadays, the vast majority of ailments are thought to be caused by the rapid environmental changes that surround individuals and particular women. In addition to physical, biochemical, genetic, and socioeconomic aspects, human mental and physical wellness need greater focus for survey and early exploration about the tendency of developing signs of certain underlying diseases and certain types of cancer as consequences of climate conditions. Thus, the purpose of this review is to record the association between Iraq's changing environment and the prevalence of various infectious diseases and malignancies.